2008
DOI: 10.1038/sj.bdj.2008.1026
|View full text |Cite
|
Sign up to set email alerts
|

Tools to share good chairside teaching practice: a clinical scenario and appreciative questionnaire

Abstract: VERIFIABLE CPD PAPERThis article provides a scenario for analysis of good chairside teaching practice to serve as a starting point for continued discussion in this complex fi eld. Documented issues of good chairside teaching practice are cross-referenced to a clinical scenario with explanations in the form of a commentary. This provided the context for generating a set of questions that are provided as tools to support good chairside practice. These tools are designed to be used with 'Appreciative Inquiry', wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…These behaviours relate to inter‐personal conduct, communication and the learning environment. Interpersonal behaviours that are deemed useful in clinical teachers are enthusiasm (12), empathy (13), ‘putting yourself into their shoes’ (14), approachability (14), reassurance (13), and compassion and caring (13). Effective communication that supports learning includes listening to students (5), attentive silence (which communicates that the teacher is paying attention and gives the learner time to think) (9), purposeful eye contact (to engage learners who require special teacher attention) (9), tracking (nods and grunts that indicate understanding and general approval) (9), and encouraging students to participate actively in discussion (5).…”
Section: Teaching For Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…These behaviours relate to inter‐personal conduct, communication and the learning environment. Interpersonal behaviours that are deemed useful in clinical teachers are enthusiasm (12), empathy (13), ‘putting yourself into their shoes’ (14), approachability (14), reassurance (13), and compassion and caring (13). Effective communication that supports learning includes listening to students (5), attentive silence (which communicates that the teacher is paying attention and gives the learner time to think) (9), purposeful eye contact (to engage learners who require special teacher attention) (9), tracking (nods and grunts that indicate understanding and general approval) (9), and encouraging students to participate actively in discussion (5).…”
Section: Teaching For Learningmentioning
confidence: 99%
“…A clinical learning environment that counters fear of failure is created through showing students respect (5), encouraging students to bring up problems (5), being available and receptive (encouraging students to ask questions and seek assistance) (15), ‘getting off the pedestal’ (relates own learning experiences to students, including problems) (15), being fun and easy to work with (cooperative, positive attitude, enjoys teaching) (15), understanding and remembering sources of stress in students’ lives (15), and refraining from ‘having favourites’ (15). Providing support in a non‐threatening way is helpful (14). Ramani (16) suggests that learners should be challenged without humiliation –‘augmented by gentle correction when necessary’ (p. 113).…”
Section: Teaching For Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…65 A willingness to share teaching methods and theories and understandings of student learning at the chairside is likely to create an overall improvement in clinical teaching. This is the process that we recommend in our paper presenting tools for dissemination of good chairside teaching practice 3 where it is envisaged that dental tutors will be publishing, presenting or discussing aspects of student learning or their teaching in the dental clinic. A further aspect of scholarship that follows on from this is the way in which, by creating a forum for discussion and debate about elements of chairside teaching, ideas and actions are challenged and development opportunities are created.…”
Section: Scholarshipmentioning
confidence: 99%
“…Watkins et al in 2016 reviewed the role of AI as an intervention for positive change in nursing practice in terms of fostering bonds, reducing defensiveness, and improving patient care 24 . There is yet only limited literature in dentistry on AI: Zakariasen et al in 2002 found AI to be very helpful for dentists to create a dynamic vision of their ideal future practices, 25 and Sweet et al in 2008 recommended clinical scenarios and appreciative questionnaires as tools to share best practices in dental chairside teaching 26 . To our knowledge, the AI approach has not previously been used to identify strategies that may help dental students tackle failure in academics.…”
mentioning
confidence: 99%